Armed with Abundance : Consumerism and Soldiering in the Vietnam War - Lair, Meredith H. (Book collections on Project MUSE., 2011)
In this ms., Meredith Lair seeks to recalibrate the way Americans think about their wars by addressing non-combat experiences of American soldiers in Vietnam. Though only one in four Vietnam veterans served in combat--and likely even fewer--both popular representations and scholarly treatments of the war focus on combat and its after-effects, erasing comfort, recreation, and fun from the picture. In this ms, Lair instead paints a provocative picture of the Vietnam War in which beauty and ice cream take precedence over the bullets, as they often did for Americans who served there. Lair uncovers.